Meta Analisis : Pengaruh Model Pembelajaran Quantum Terhadap Hasil Belajar Siswa - Sawitri, Yolly; Azis, Hasbi (Jurnal Penelitian Pembelajaran Fisika, 2020)
The 21st century is marked as a century of openness or a century of globalization, meaning that human life experiences fundamental changes that are different from the order of life in the previous century. 21st Century is also known as the era of knowledge, which is all alternative efforts to meet the needs of life in a variety of more knowledge-based contexts. The 21st century education paradigm has experienced a shift marked by differences in learning orientations. The learning of the previous century emphasized literacy in reading, writing, and mathematics, where in the 21st century they were used as the basis for developing new literacy, namely human, data and technological literacy which is very important to face the current and future globalization era. . This study aims to analyze the effectiveness of learning using the Quantum Learning model of 21st century knowledge, attitudes and skills competencies of students. Analysis in terms of learning material, teaching materials and media, types of research, research designs and research results. As with similar research in general, this meta-analysis is expected to be useful in the field of education, especially Physics teachers in choosing learning materials, teaching materials used and measuring the competency of students right when applying Quantum Learning learning models in schools. This research method is a meta-analysis with a sample of 10 articles in national journals.